2022
DOI: 10.1002/admi.202101745
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and Interface Studies of the Structure‐Controlled Polyimide with Smooth Copper for High‐Frequency Communication

Abstract: Fan‐out wafer‐level packaging (FOWLP) is expected to become the dominating trend in millimeter wave and 5G communication. However, the reliability faces enormous challenges due to the inherent poor adhesion between the insulating layer of polyimide (PI) and copper wirings in FOWLP. Herein, adhesive polyimide (API) with improved adhesion on smooth Cu by the introduction of benzimidazole and siloxane structure is reported. The results prove that the adhesion strength is increased by 191.46% compared with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Thus, the peel strength can reach 1.1392 N mm −1 . 101 Fig. 6 shows that stripping occurs inside the molecular chains of the compounds made into membranes, i.e.…”
Section: Insulation Base Film and Its Modification Progress For 2l-fcclmentioning
confidence: 99%
“…Thus, the peel strength can reach 1.1392 N mm −1 . 101 Fig. 6 shows that stripping occurs inside the molecular chains of the compounds made into membranes, i.e.…”
Section: Insulation Base Film and Its Modification Progress For 2l-fcclmentioning
confidence: 99%
“…To improve the interface adhesive performance, Zhong et al 16 reported an adhesive polyimide (PI) via the introduction of benzimidazole and siloxane structure adhered with smooth Cu, and the adhesive strength increased by 191.46% in comparison with that of the conventional PI. However, this manufacturing process requires a specific substrate and is not suitable for general substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The intrinsic water contact angle (WCA) of pure PI films is low (≈50°-80°), unable to meet the requirements of hydrophobic properties for IC chip packaging and flexible wearable devices. [14][15][16][17][18][19][20] Therefore, it is necessary and meaningful to improve the hydrophobic properties of PI films from the perspective of intrinsic structure and surface microstructure design while ensuring excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%